2013
DOI: 10.3852/12-088
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic position of Postia s.l. (Polyporales, Basidiomycota) from Patagonia, Argentina

Abstract: We investigated the phylogenetic relationships of Postia species from Patagonia with rDNA ITS and LSU sequences, together with morphological, cultural and biological features. All species in the genus were included in a ''Postia clade'' irrespective of whether their spores were thin-or thick-walled. This clade is characterized by tetrapolar mating, a normal nuclear behavior, metachromatic generative hyphae and absence of fiber hyphae in culture. One subclade merged the austral taxa P. pelliculosa and P. puncta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Pildain & Rajchenberg (2013) sequenced the ITS and nLSU regions from eleven species of Postia and related species; their phylogenetic analysis indicated that most species in Postia and Oligoporus were monophyletic, but supported the transfer of P. placenta into its own genus as Rhodonia placenta , in agreement with previous studies (Boidin et al 1998, Kim et al 2001, Binder et al 2005, Niemelä et al 2005). Ortiz-Santana et al (2013) investigated the phylogenetic relationships among members of the antrodia clade with molecular data from ITS and nLSU regions; in their study, species of Postia s.lat.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Pildain & Rajchenberg (2013) sequenced the ITS and nLSU regions from eleven species of Postia and related species; their phylogenetic analysis indicated that most species in Postia and Oligoporus were monophyletic, but supported the transfer of P. placenta into its own genus as Rhodonia placenta , in agreement with previous studies (Boidin et al 1998, Kim et al 2001, Binder et al 2005, Niemelä et al 2005). Ortiz-Santana et al (2013) investigated the phylogenetic relationships among members of the antrodia clade with molecular data from ITS and nLSU regions; in their study, species of Postia s.lat.…”
Section: Introductionsupporting
confidence: 85%
“…In fact, Postia is the oldest name among the competing genera. Some mycologists combined the brown rot taxa of Tyromyces into Postia (Renvall 1992, Niemelä et al 2005, Wei & Dai 2006, Hattori et al 2011, Cui & Li 2012, Pildain & Rajchenberg 2013). With more species recognized in Postia , the definitions of the genus and related genera remain murky, and so are the genetic relationships among these fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also utilized three ITS sequences provided by Viktor Papp as well as 63 ITS and 28S sequences from the INSDC (Suppl. 1), based on BLAST searches and Ortiz-Santana et al 2013, Pildain & Rajchenberg (2013), Shen et al (2014), and Justo et al (2017).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Yao et al (2005) showed that three ITS-sequence-based groups were present in England, but they could not connect those groups to existing names. Ortiz-Santana et al (2013) and Pildain & Rajchenberg (2013) presented genus-level phylogenies that included representatives of the Postia caesia complex. Both concluded that the Postia caesia complex belongs to the genus Postia, but did not touch upon species concepts.…”
Section: Introductionmentioning
confidence: 99%